(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
New records of Lepidoptera Tortricidae for the Greek and Spanish fauna are reported. Acleris lorquiniana (Duponchel), Oxypteron eremicum (Walsingham), Cnephasia genitalana Pierce & Metcalfe, Choristoneura diversana (Hubner) and Clepsis burgasiensis (Rebel) are new for Greece. Cnephasia gueneana (Duponchel) and Cnephasia ecullyana Réal are new for Spain. O. eremicum is mentioned for the first time in Europe.